The Proximal Tibia Loses Bone Mineral Density After Anterior Cruciate Ligament Injury: Measurement Technique and Validation of a Quantitative Computed Tomography Method - Erick M. Marigi, M.D; David R. Holmes, Ph.D; Naveen Murthy, M.D; Bruce A. Levy, M.D; Michael J. Stuart, M.D; Diane L. Dahm, M.D; Peter C. Rhee, D.O., M.Sc; Aaron J. Krych, M.D (Elsevier, 2021)
Purpose: To develop a standardized method for tibial tunnel volumetric bone mineral density (BMD) analysis with quantitative computed tomography (qCT) using cadaveric specimens to provide validation of this technique on a healthy control population and to determine whether osteopenia occurs following an anterior cruciate ligament (ACL) injury.Methods: qCT was used to develop a volumetric BMD (mg/cm3) measurement technique throughout the region of a standard tibial tunnel. This method was applied to 90 lower extremities, including 10 matched cadaveric knees, 10 matched healthy knees, 25 ACL-injured knees, and 25 contralateral ACL-uninjured knees. The mean total and segmental (proximal, middle, and distal) tibial tunnel BMD were analyzed. Results: The mean entire tibial tunnel BMD measured 165.8 ± 30.5 mg/cm3 (cadaver), 255.9 ± 28.2 mg/cm3 (healthy control), 290.3 ± 36.4 mg/cm3 (ACL-injured), and 300.1 ± 35.1 (ACL-uninjured). Segmental tibial tunnel BMD demonstrated distal one-third segments as the greatest areas of BMD, followed by proximal one-third, and middle one-third for all cohorts with all pairwise comparisons (P < .001). The mean BMD was significantly greater in the uninjured extremity compared with the injured extremity in the entire tunnel (290.3 vs 300.1; P < .001), proximal (271.2 vs 279.1; P = .002), middle (167.6 vs 179.6; P < .001), and distal segments (432.7 vs 441.7; P = .004) at an average of 8 weeks following ACL injury. Conclusions: A standardized method to quantitatively measure the volumetric BMD within the region of a standard tibial tunnel for ACL reconstruction was successfully developed and validated. Significant osteopenia of the injured knee occurs following ACL injury when compared with the contralateral uninjured knee. This observation has potential clinical implications for ACL graft tibial fixation and healing. Level of Evidence: Descriptive diagnostic study, Level III.